New type of eigen oscillations based on evanescent waves - Ayzatsky, M.I. (Вопросы атомной науки и техники, 2001)
In this paper we represent the results of investigations of the electromagnetic waves in a layered dielectric that is limited from one side by a metal plate. There are electromagnetic oscillations, which evanesce in the direction of periodicity and propagate along the perpendicular direction, so they can be treated as surface waves. Existence of such waves gives possibility to create resonators filled by a layered dielectric with new type of eigen oscillations based on these evanescent waves.